PERILAKU BULLYING DI PONDOK PESANTREN ULUMUL QUR'AN BEBESEN, ACEH TENGAH. - Musdiansyah Lingga; Nurjannah Nurjannah (Universitas Islam Ahmad Dahlan, 2023)
Bullying is a phenomenon that occurs in various environments, including in Islamic boarding schools. This study aims to describe bullying behavior that occurs at the Ulumul Qur'an Bebesen Islamic Boarding School, Central Aceh. The data for this study were collected through observation, interviews given to pesantren students and staff. The results of the study show that bullying behavior is present in the context of this Islamic boarding school. Some forms of bullying observed include verbal abuse, psychological intimidation. The motivations behind this bullying behavior vary, including the desire to dominate, personal satisfaction, feelings of inferiority, and social differences. Factors that play a role in the occurrence of bullying at the Ulumul Qur'an Bebesen Islamic Boarding School include a lack of adequate supervision, a lack of understanding of the harmful effects of bullying, and a lack of efforts to address this problem. In addition, certain culture and social norms in Islamic boarding schools can also influence the prevalence of bullying behavior. This research highlights the importance of awareness and effective interventions to overcome the problem of bullying in Islamic boarding schools. Developing educational programs that teach about diversity, empathy, tolerance, and effective communication can help reduce bullying behavior. In addition, involving pesantren staff, parents and the community in efforts to prevent and deal with bullying is also an important step.